Simulation Study to Enhance the Efficiency of Switching Devices using the Combinations of Diodes in Various Networks. Issue 1 (23rd February 2023) - Tiwari, Satyendra Nath; Khadarabad, Ghouse Mohiuddin; Pandey, Shri Prakash; Pandey, Anoop Kumar; Singh, Vijay
Abstract: In this communication, PSpice simulation software is used to design and characterize reverse biasing modes in series and parallel combinations. Using multiple diodes of similar types, how the breakdown voltage and power dissipation vary in parallel and series modes in reverse bias is investigated. In this paper, correlation equations and correlation factors between voltage and current in both series and parallel combinations using n = 1‐5 diodes in reverse bias are also found. The second‐order correlation equation between voltage and current provides a new way for designing new networks of PN junction diodes for better power gain. The mathematical formulation for applied voltage and average current of n = 1‐10 diodes in parallel and series combinations is also calculated, which can help researchers to design new network circuits for switching devices in the electronics industry.